STRATEGIC CORPORATE GOVERNANCE AND ESG INTEGRATION - Abduganieva Mumtozbegim Abdurahim kizi (Journals Park Publishing, 2025)
The importance of strategic corporate management is increasing in the modern business environment. Effective management methods play an important role in making companies competitive. At the same time, environmental, social and governance factors also remain an integral part of corporate strategy. ESG integration is important in ensuring the long-term success of companies, as well as increasing their responsibility towards society and the environment.
Keywords: Business, strategic corporate management, company, competition, methods, analysis, energy efficiency improvement.